Traditions and Culture of Enam Kaum as a Source of Strengthening Ethnopedagogy in Mukomuko Bengkulu - Muhammad Ilham Gilang; Ramedlon Ramedlon; Tasri Tasri (Indonesian Journal of Social Science Education (IJSSE), 2025)
This research aims to find out the customs and culture that exist in Mukomuko, which can then be used as a source of strengthening ethnopedagogy in the world of education. The research objectives are (1) what are the customs and culture of the Enam Kaum in Mukomuko Regency?, (2) what are the customs and culture of the Enam Kaum Mukomuko as a source of ethnopedagogy? The research method used is qualitative, with observation, documentation and interview techniques. Meanwhile, data analysis uses an interactive analysis model. The research results reveal that, firstly, historically, the original Mukomuko people came from West Sumatra, so they have many cultural and customary similarities with Minangkabau. The customs and culture that are strong in Mukomuko are the Enam Kaum, which is a typical Mukomuko kinship system. Consisting of the Berenams in the Upstream, the Beresams in the Downstream, the Eight Tribes in the Middle, the Five Tribes, the Fourteenth Tribes, and the Gersik Tribes. Second, the customs and culture of the Six Mukomuko Clans are very significant as a source of strengthening ethnopedagogy, with at least four components, namely; intangible traditions, material traditions, community history and strong Islamic religious beliefs. These four things can be a source of strengthening ethnopedagogy in the world of education in Mukomuko Regency.